The effectiveness of pro-math challenge module to improve knowledge, perception, attitude and inclination of students in mathematics subject / Anis Zafirah Azmi ... [et al.] - Azmi, AzmiAnis Zafirah; Mohamad Razi, Nor Faezah; Jufiza, A. Wahab; Anisah, Abdul Rahman; Ahmad Nur Azam, Ahmad Ridzuan; Zulkifli, Mohd Ghazali (UiTM Press, 2020)
This paper presents an empirical finding from a research that implementing a Pro-Math Challenge module for form three students in Sekolah Menengah Kebangsaan Gunung Rapat Setia, Ipoh, Perak Malaysia. The objective of this study is to identify the effectiveness of the module in improving students’ mathematical knowledge, which categorized as the Science, Technology, Engineering and Mathematics (STEM) proficiencies. Implemented in a STEM program, the students’ responses on the module were analyzed with a questionnaire survey to measure four criteria namely knowledge, perception, attitude and inclination. The results from a Wilcoxon Signed-rankas test have revealed that each of the criteria has a statistically significant difference on the increment of students’ understanding after the Pro Math Challenge module was implemented. Overall, half of the students strongly agree that the Pro-Math Challenge module implemented in the STEM program was beneficial to them and has given a good impact to them.